(untitled) (Al-Qamar, 2022)
The idea of ​​reviving or renewing religious thought was not an innovation according to Iqbal. Rather, if we browse through the references of Islamic history, we find many such attempts, because development in human thought is a possibility, and none of us can deny this fact that human thought is renewed and developed in every time and place, whether this Thought is related to one of the religions, the affairs of life, or a matter of worldly matters. From this point of view, thinking about reviving religious thought and the serious attempts that have been made in this field in the Islamic world are links of a golden chain to revive human thought, especially Islamic thought and the efforts of Allama Muhammad Iqbal in The Indian subcontinent to reform the theory of Islamic life is well known in the scientific and intellectual circles. We try to highlight it in this article, God willing.